Prospects of Trademark Registration To Recover The Economic of MSMEs Actors in Service Sector after The Pandemic - Dedi Jaya; Hari Sutra Disemadi (Universitas Widya Gama Malang, 2022)
MSMEs are businesses that can be run by all people who want to start a business with small capital. Q, MSMEs have strategic role in building Indonesian economy. However, the growth of MSMEs is experiencing a slump due to COVID-19. On March 11, 2020, WHO as a legal world health organization declared the COVID-19 as a pandemic. MSMEs have become solution to increase the welfare of Indonesian citizen, since the issue of welfare itself is not an easy to realize. To support MSMEs in increasing the welfare, it is necessary for the government to take action in pushing MSME actors to registrate their trademarks as part of intellectual property which is very important in the economic recovery. Based on these problems, this study uses non-doctrinal research methods to examine trademark regulation in Indonesia, the awareness of MSME actors on the importance of trademark protection, and the relation of trademark registration as an effort to recover the MSME economy after the pandemic. The result of this study indicates that the regulation regarding trademark protection is contained in Indonesian Trademark & Geographical Indication Law. Additionally, the study reveals that there are several MSME actors who aware that a brand must be protected because it is an intellectual property, but there are also MSME actors who do not aware about this issue. In fact, the urgency of trademark registration is considered to be the part of efforts in recovering the economy of MSMEs after the COVID-19 pandemic, this is because after registering the trademark, it automatically has economic value.